2008
DOI: 10.1167/iovs.08-1957
|View full text |Cite
|
Sign up to set email alerts
|

Duplication and Divergence of Zebrafish CRALBP Genes Uncovers Novel Role for RPE- and Müller-CRALBP in Cone Vision

Abstract: The results suggest that cone photoreceptors incorporate 11-cis-retinoids derived from the rod and cone visual cycles into their visual pigments and that Müller-CRALBP participates in the cone visual cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 48 publications
1
51
1
Order By: Relevance
“…Collery et al additionally used an antibody against cone blue-opsin to test for cone integrity after Cralbp b knock-down. In concordance with our results, they did not detect any abnormalities in cone morphology or opsin expression (Collery et al, 2008;Fleisch et al, 2008). Our data in zebrafish mirror the data published in the Cralbp knock-out mouse model.…”
Section: Subfunctionalization Of Zebrafish Cralbp Provides Evidence Fsupporting
confidence: 93%
See 3 more Smart Citations
“…Collery et al additionally used an antibody against cone blue-opsin to test for cone integrity after Cralbp b knock-down. In concordance with our results, they did not detect any abnormalities in cone morphology or opsin expression (Collery et al, 2008;Fleisch et al, 2008). Our data in zebrafish mirror the data published in the Cralbp knock-out mouse model.…”
Section: Subfunctionalization Of Zebrafish Cralbp Provides Evidence Fsupporting
confidence: 93%
“…Collery et al reported that knock-down of both zebrafish Cralbp proteins resulted in a significant reduction in the number of saccades in the OKR (Collery et al, 2008). In contrast to that, we found that visual performance, measured as a contrast sensitivity function, was significantly impaired in zebrafish larvae injected with the Müller cell-specific cralbp b MO, but cralbp a MO-injected fish did not differ from wildtype controls (Fleisch et al, 2008) (Figure 5).…”
Section: Cone Photoreceptors Use Both the Canonical And The Intra-recontrasting
confidence: 73%
See 2 more Smart Citations
“…However, cone vision of RPE65-knockdown larvae remained functional as demonstrated by behavioural tests and by metabolite profiling for retinoids (Schonthaler et al 2007). The zebrafish genome also contains two CRALBP orthologues: rlbp1a and rlbp1b (Collery et al 2008;Fleisch et al 2008). CRALBP-a is exclusively expressed in the RPE, whereas CRALBP-b is localized to Mü ller cells.…”
Section: Diversity Of the Visual Retinoid Cycle In Vertebrates (A) Romentioning
confidence: 99%